TINJAUAN HUKUM ISLAM TERHADAP OPERASIONAL AKAD SALAM DALAM JUAL BELI SECARA ONLINE - Imam Fawaid (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
One of the developments in information and communication technology, among others, is the virtual world technology or commonly known as the internet (interconnection network). The Internet as a medium for information and electronic communication has been widely used for various activities, including browsing, searching for data and news, sending messages to each other via e-mail, communicating through social networking sites, and including for trading. Trading activities using internet media are known as electronic commerce, or e-commerce for short.Trading transactions via the internet are different from shopping or trading transactions in the real world. The payment method commonly used is for the buyer to transfer an amount of money to the seller.The results of this research are the mikanism of the salam contract carried out by the online system must be in accordance with Islamic law, meaning that in the delivery of goods carried out online, there must be clarity of the products that are loaded on the website according to reality, and the method of transaction must be harmonious and compliant. the terms of the salam contract that have been determined by Islamic law, and the products / goods promoted through the website are 100% in accordance with reality. Keywords: ;;